Reinterpretasi Teater Tradisi Dalam Perspektif Patronase - Heny Purnomo (Sekolah Tinggi Kesenian Wilwatikta Surabaya, 2022)
Traditional art theatre that is owned and attached to a community can be used to understand the culture of a society. This is true because traditional arts and theater reflect the personality and way of life of the broader community. Traditional theatrical productions that are held live and move from one location to another (tobong) are becoming increasingly rare and are currently on the verge of extinction. Additionally, every performance is always in competition with other arts that have been transformed by other technological media television. Many forms of presentation produced using stage visuals were influenced by ludruk tobong, which had its peak in the 1970s and 1980s. Ludruk Tobong, a traditional populist-based theater, was born and raised in a society that has served as its primary patron. Every staging of a play incorporates